299 Increasing incidence of sex cord-stromal tumors in the United States. (13th November 2020) - Ratnaparkhi, R; Liao, C; Chan, A; Tian, C; Darcy, KM; Maxwell, L; Knapp, DS; Chan, JK
Abstract : Introduction: The incidence of ovarian cancer has decreased in the United States since the 1980s, due to decreasing incidence of epithelial ovarian cancers. The purpose of this study was to analyze trends in incidence of non-epithelial ovarian cancers. Methods: Data were obtained from the United States Cancer Statistics (USCS) database from 2001 to 2016. Age-adjusted incidence per 100, 000 women and annual percent change (APC) in incidence were calculated using SEER*Stat and Joinpoint Software. Results: 18, 346 women were diagnosed with non-epithelial ovarian tumors. 6, 720 had sex cord-stromal tumors (SCST), of which 82.3% were granulosa cell tumors and 9.7% were Sertoli-Leydig cell tumors. 10, 035 were germ cell tumors. The age-adjusted incidence rate was 0.28 for SCST, 0.24 for granulosa cell tumors, and 0.41 for germ cell tumors. Blacks had the highest incidence of SCST (0.61). Over a sixteen-year period, the overall incidence of SCST increased 1.70% annually (95% CI 1.13, 2.28; p<0.001), and the incidence of granulosa cell tumors increased 2.24% annually (95% CI 1.60, 2.88; p<0.001). The incidence of mixed germ cell tumors also increased 3.4% annually (95% CI 1.89, 4.86; p<0.001). However, the incidences of Sertoli-Leydig cell tumors and other subtypes of germ cell tumors were unchanged in the same time period. Conclusions: The incidence of sex cord-stromal tumors is increasing in the United States. Given prior studies suggesting risk is minimally affected by reproductive or lifestyle factors, further research is needed to elucidate mechanisms underlying this trend.